2020
DOI: 10.2147/ott.s247655
|View full text |Cite
|
Sign up to set email alerts
|

<p>MicroRNA-375 Targets ATG14 to Inhibit Autophagy and Sensitize Hepatocellular Carcinoma Cells to Sorafenib</p>

Abstract: Sorafenib has revolutionized treatment of hepatocellular carcinoma (HCC), but its efficacy is limited by drug resistance. Autophagy is the process by which cellular components are transported to lysosomes for degradation, which promotes energy production and production of macromolecular precursors. Studies have suggested that the cytoprotective function of autophagy may contribute to chemoresistance or targeted drug resistance in cancer cells. We investigated the effects of miR-375 and autophagy-related protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 52 publications
0
26
0
Order By: Relevance
“…In another study, by transfecting miR‐375 mimic into Huh7 cells, a marked increase of apoptosis rate of Huh7 cells is observed 10 . Additionally, miR‐375 can enhance the sensitivity of HCC cells to sorafenib by the regulation of ATG14 expression 22 . In our current research, the inhibitory effect of miR‐375 on HCC development was further verified by using SNU‐398 and HepG2 cells, and we demonstrated that circ_0072088 contributed to the dysregulation of miR‐375 in HCC.…”
Section: Discussionmentioning
confidence: 94%
“…In another study, by transfecting miR‐375 mimic into Huh7 cells, a marked increase of apoptosis rate of Huh7 cells is observed 10 . Additionally, miR‐375 can enhance the sensitivity of HCC cells to sorafenib by the regulation of ATG14 expression 22 . In our current research, the inhibitory effect of miR‐375 on HCC development was further verified by using SNU‐398 and HepG2 cells, and we demonstrated that circ_0072088 contributed to the dysregulation of miR‐375 in HCC.…”
Section: Discussionmentioning
confidence: 94%
“…The assistance of miR-375 in anti-tumor therapy has already been uncovered. MiR-375 augmented the susceptibility of HCC cells to sorafenib by targeting the autophagy-related gene, ATG14 [17]. MiR-375 also inhibited the survival of fulvestrant-resistant breast cancer cells by restraining autophagy [18].…”
Section: Discussionmentioning
confidence: 99%
“…This blunted autophagy response contributes to increased susceptibility of HCC cell lines and xenograft models to hypoxic stress. In a similar trend, the same miR-375 blocks ATG14-mediated autophagy in sorafenib-treated Huh7 and HepG2 cells and increase sensitivity to sorafenib [ 8 , 91 ]. In another study, overexpression of miR-132 in HCC cells and tissues blocks PIK3R3-dependent autophagy but promotes apoptosis.…”
Section: Ageingmentioning
confidence: 95%